THE INFLUENCE OF CLASSICAL MUSIC THERAPY AND LAVENDER AROMATHERAPY CANDLE ON ANXIETY LEVELS DURING THE FIRST STAGE OF ACTIVE LABOR - Nelly Nugrawati; Nur Ekawati; Ayu Wijaya; Andi Muhammad Adam (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Childbirth is eagerly anticipated by married couples, yet it can lead to anxiety due to its intense nature. Therefore, support from spouses, families, and the community is crucial for the well-being of both mother and child. This study aims to explore the impact of classical music therapy and lavender aromatherapy on anxiety levels during active labor's first phase. Using a pre-experimental quantitative approach, the research employs a one-group pretest-posttest design, focusing on mothers in active labor's first phase in the Ballaparang health center area. Sampling involved 44 third-trimester pregnant women selected through simple random sampling. Data analysis utilized the Wilcoxon test. Findings revealed that prior to intervention, most respondents experienced moderate anxiety (47.7%), while after intervention, the majority experienced mild anxiety (45.5%). Bivariate analysis indicated a significant influence of classical music therapy and lavender aromatherapy on reducing anxiety levels among mothers in active labor's first phase, with a p-value of 0.000. Pre-test anxiety scores were higher than post-test scores, suggesting a decrease in anxiety levels following intervention.